The process of developing an emotional nexus between the self and an uncanny geography: An autoethnography - Bogac, Ceren (Elsevier, 2020)
In this paper, I aim to explore my nexus with a prohibited place and its emotional meaning, reflected over a 30-year period. This exploration involves evocative autoethnography in which I discuss my process of bonding to a place. Varosha, a quarter originally built by the Greek Cypriots in Famagusta, Cyprus, was unwillingly abandoned by them after the island was fragmented in 1974. Since then, entry to this place has remained prohibited. My childhood and adolescent years were centered in this unusual geography. Varosha is known as a “ghost town” in international media, and yet, I would not define it as a specter, rather as an uncanny geography becauseI have experienced it as both a familiar and an unfamiliar place. In this paper, I have identified this bond as an “empathic place attachment.” I believe that emotions evoked toward a prohibited place are a rare fabric of our personal geographies that provide a new assessment of the nexus between the self and place.
Boğaç, C. (2020). The process of developing an emotional nexus between the self and an uncanny geography: An autoethnography. Emotion, Space and Society, ISSN: 1755-4586, 36, pp- 1-8
Keywords: Place attachment; Autoethnography; Uncanny geography; Emotions; Varosha; Famagusta Ecocity Project